Implementation of the Jakarta Elderly Card Program in Meeting the Basic Needs of the Elderly - Rizal*, Ahmad; Susilahati, Susilahati (Universitas Syiah Kuala, 2023)
Research on the Implementation of the Jakarta Elderly Card Program in Fulfilling the Basic Needs of the Elderly is motivated by the increasing number of poor elderly people in the Special Capital Region of Jakarta (DKI) Jakarta, including the number of poor elderly people in the Jagakarsa village. Along with this, the DKI Provincial Government has launched the KLJ Program (Jakarta Elderly Card) as an effort to meet the basic needs of the poor elderly. However, the implementation of this KLJ is often in the spotlight of various parties, because it is assumed to be less useful and not on target. The purpose of this study was to describe how the implementation of the KLJ program in meeting the basic needs of the elderly. The research method uses a qualitative research approach. Data was collected through interviews, observation and documentation. The main theory used is the theory of David C Korten which states that to find out how the implementation of a program can look at the dimensions of the program itself, then the organization of its implementation and the program's goals. The results showed that the implementation of the program could increase the number of poor elderly people. This is because there is a clear concept of this program and there is strong support from the program implementing elements, both the city government and the community. This is what causes the inconsistent implementation of aid distribution. In general, assistance is used to meet the basic needs of the elderly. Recommendations from this research are the need for an official website that is easily accessible to the public and the need for consistent distribution of time.